Endophytic fungi for plant disease management: Antagonistic potential and molecular characterization - Shruthi, C; Nagaraju, K; Tamilvendan, K; Muthuraju, R; Mudalgiriyappa (Plant Science Today, 2026)
Browntop millet (Brachiaria ramose L.), a nutritionally rich and climate-resilient minor millet, is increasingly valued in sustainable agriculture; however, its productivity is severely affected by leaf blight caused by Bipolaris setariae. The present study investigated the potential of endophytic fungi associated with Browntop millet as eco-friendly biocontrol agents for managing this disease. A total of 64 endophytic fungal isolates were obtained from healthy plant tissues collected across different agroclimatic zones of Karnataka. Pathogenicity assays confirmed B. setariae as the causal agent of leaf blight. Dual culture assays revealed strong antagonistic activity by several isolates with REF-23 (88.12 %), LEF-63 (86.78 %) and GEF-13 (78.91 %), showing inhibition comparable to the standard biocontrol agent Trichoderma harzianum. These efficient isolates also exhibited multiple plant growth-promoting and other traits, including phosphate solubilization, ammonia, siderophore production and hydrogen cyanide production. Endophytic fungal isolates from Browntop millet showed strong antagonism against B. setariae, mainly through extracellular hydrolytic enzymes (cellulase, xylanase, amylase and lipase). REF-23 and LEF-63 exhibited the widest enzyme profiles and highest hydrolytic indices, indicating superior mycolytic potential. Molecular identification confirmed the taxonomic diversity of effective endophytes REF-23 and LEF-63 as Paecilomyces lilacinus and Chaetomium spp. respectively. Along with pathogen suppression, these fungi displayed multiple plant growth-promoting traits, highlighting their dual role in disease management and growth enhancement. Overall, Browntop millet-associated endophytic fungi represent promising, eco-friendly bioagents for integrated leaf blight management and sustainable crop productivity.